Foraging Paths of Breeding Leach’s Storm-Petrels in Relation to Offshore Oil Platforms, Breeding Stage, and Year - Collins, Sydney M.; Hedd, April; Fifield, David A.; Wilson, David R.; Montevecchi, William A. (Frontiers in Marine Science, 2022)
The global population of Leach’s Storm-Petrels (Hydrobates leucorhous), the smallest and most abundant breeding seabird species in eastern Canada, has declined substantially in recent decades. The species is listed as “Threatened” by the Committee On the Status of Endangered Wildlife in Canada (COSEWIC) and as “Vulnerable” by the International Union for Conservation of Nature (IUCN). Fatal attraction to anthropogenic light is a major risk for Leach’s Storm-Petrels and many other nocturnal seabirds. From May to September each year, Leach’s Storm-Petrels in eastern Canada breed in island colonies and travel many hundreds of kilometers to obtain prey for themselves and their chick. At the species’ largest colonies in eastern Newfoundland, brightly illuminated oil production platforms intersect breeding storm-petrels’ foraging paths. The level of risk posed by these platforms is poorly understood. GPS tracking from 2016 to 2021 at one of the world’s largest colonies revealed considerable similarity in foraging trip distance, location, and behavior (inferred from Hidden Markov Models) among years, and a decrease in trip distance and duration between incubation and chick-rearing. Leach’s Storm-Petrels flew within the light catch-basin of an oil platform in 17.5% of trips, and the birds tended to transit rapidly past platforms during the day when light attraction is minimal. Exposure to oil platforms at night occurred in only 1.1% of trips. Despite our findings, Leach’s Storm-Petrels are known to strand on oil platforms in large numbers, especially during the fledging period. In addition, storm-petrels migrate over great distances and are likely exposed to brightly illuminated oceanic oil platforms outside the breeding season. Our results emphasize the need to focus conservation research on risks during migration and winter, and on juveniles and immature birds.